USING E-BOOKS TO IMPROVE ENGLISH READING COMPREHENSION OF SECONDARY SCHOOL STUDENTS - Rahmatillah Rahmatillah; Syarifuddin Dollah; Munir Munir (State University of Makassar, 2026)
This study, conducted on 30 eighth grade students at SMP Negeri 27 Makassar using a pre-experimental one-group pretest-posttest design, aimed to evaluate the effectiveness of e-books in improving English reading comprehension and gauge student interest in the digital medium. The results showed that e-books were highly effective. Students' reading comprehension scores saw a statistically significant increase (significance value of 0.000), rising sharply from a